Odpowiedzi

2010-03-08T19:37:47+01:00
A) ⅓x-2=x+2
1/3x-x=4
-2/3x=4/-2/3
x=-6
b) a- 6/7x=4/7
c) 6 (¼x - 2 )=18
d) x/6 - ⅙ = 1
e) -2 (2x-1)= x/3
f) 2/5 (3-x)= -2
g) 3/4 (2-3x)= -6
h) ⅕ (x-3) = 9 - x
2010-03-08T19:46:16+01:00
A) ⅓x-2=x+2
-⅔x=4 |×3
-2x = 12
x=-6

b) a- 6/7x=4/7 |x7
7a - 6x = 4

c) 6 (¼x - 2 )=18 |:6
¼x-2=3 |x4
x-8=12
x=20

d) x/6 - ⅙ = 1 |x6
x -1 = 6
x =7

e) -2 (2x-1)= x/3 | x3
-6(2x-1)=x
-12x +6 =x
-13x = -6
x = 6/13

f) 2/5 (3-x)= -2 | x5
2(3-x)=-10
6-2x = -10
-2x = -8 | :(-2)
x = 4

g) 3/4 (2-3x)= -6 |x4
3(2-3x)= -24
6-9x =-24
-9x=-20 | : (-9)
x= 2,(2)

h) ⅕ (x-3) = 9 - x | x5
x-3 = 45 - 5x
6x = 42 |:6
x = 7